Deep crustal structure along the profile between Syowa and Mizuho Stations, East Antarctica - Ikami, Akira; Ito, Kiyoshi; Shibuya, Kazuo; Kaminuma, Katsutada (1984)
P(論文) Three big seismic explosion experiments were carried out by the 21st and 22nd Japanese Antarctic Research Expeditions in the vicinity of Syowa Station and in the northern Mizuho Plateau in East Antarctica. Twenty-seven temporal seismic observation stations were set up along a 300-km long profile from Syowa to Mizuho Stations. Explosives were fired near Syowa Station, near Mizuho Station and at the middle point of the profile. The apparent P-wave velocity in the upper crust varies from 6.0 to 6.4 km/s, suggesting a gradual increase of the P-wave velocity with depth. Apparent velocities of 6.9 km/s for P^* and 7.9 km/s for P_n were observed from the biggest shot near Syowa Station. From the analyses of travel times and an amplitude study by synthetic seismograms, the crustal structure of the northern Mizuho Plateau was determined. The depth of the Conrad and the Moho discontinuities was determined as about 30 km and 40 km, respectively. The P-wave velocity increases from 6.0 km/s on the surface to 6.4 km/s at a depth of 13 km. At the Conrad, there is no sharp velocity discontinuity. The thickness of the transition zone is 2.4 km. Comparing our results with those in Dronning Maud Land (in the vicinity of Novolazarevskaya Station of USSR), East Antarctica, velocity values are nearly the same, but the thickness of lower crust in the northern Mizuho Plateau is about a half of that in Dronning Maud Land. departmental bulletin paper